Effect of preoperative virtual reality cartoon viewing on postoperative pain and anxiety in children undergoing tonsillectomy and adenoidectomy: A randomized controlled trial - Seda Kırhallı Mersin; Berna Dizer; Arzu Tuna (PLoS ONE, 2025)
Objective Surgery causes anxiety in children and negatively affects postoperative pain control. Various distraction methods, such as virtual reality (VR), have been shown to reduce anxiety levels and improve surgical outcomes. This study aimed to determine the effect of watching cartoons through a VR headset before surgery on systolic blood pressure, postoperative pain, and anxiety levels as primary, secondary, and tertiary outcomes, respectively, in children aged 7–12 years undergoing tonsillectomy and adenoidectomy. Methods This randomized controlled experimental study was conducted at a tertiary hospital between November 10, 2023, and June 1, 2024, among 102 children scheduled for tonsillectomy and adenoidectomy, who were randomly divided into an experimental group (n = 51; VR intervention) and a control group (n = 51; no intervention). The primary outcomes were anxiety levels measured using the Perioperative Multidimensional Anxiety Scale for Children and postoperative pain evaluated using the Visual Analog Scale. Sociodemographic characteristics and vital signs were also assessed. Results Systolic blood pressure values were significantly lower in the experimental group at than in the control group at all time points (p < 0.05). Postoperative pain values were lower in the experimental group (3.35 ± 1.43 vs. 6.53 ± 1.36, p < 0.05), with similar results observed 8 h post-surgery (1.29 ± 1.08 vs. 6.57 ± 1.17, p < 0.05). Anxiety values were also significantly lower in the experimental group (24.12 ± 11.17 vs. 69.41 ± 12.56, p < 0.05), with similar results observed 8 h post-surgery (12.35 ± 10.50 vs. 67.0 ± 11.37, p < 0.05). Conclusion VR technology, particularly through watching the Shrek cartoon, significantly reduced systolic blood pressure, pain, and anxiety levels in children undergoing tonsillectomy and adenoidectomy. Thus, VR could be an effective noninvasive tool for managing pain and anxiety in pediatric patients during the preoperative and postoperative periods. Trial registration ClinicalTrials.gov (NCT06763276).